2016
DOI: 10.1111/liv.13052
|View full text |Cite
|
Sign up to set email alerts
|

Inducing tolerability of adverse events increases sorafenib exposure and optimizes patient's outcome in advanced hepatocellular carcinoma

Abstract: In patients with advanced hepatocellular carcinoma, sorafenib dose adjustments based on inducing tolerability of relevant adverse events prolong drug exposure and maximize survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Because of the lack of reliable biomarkers for sorafenib use, dermatologic AEs related to sorafenib have become widely recognized as surrogate markers for efficacy in patients with HCC. [20][21][22] The prognostic value of these dermatologic AEs was also confirmed in our very recent multicentre clinical study of 606 HCC patients, which demonstrated that sorafenib-related dermatologic AEs may be used as clinical indicators to identify responders to sorafenib and those who are more likely to benefit from TACE-S treatment. 23 Indeed, patients who develop dermatologic AEs might constitute the ideal population in whom the addition of sorafenib would work.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Because of the lack of reliable biomarkers for sorafenib use, dermatologic AEs related to sorafenib have become widely recognized as surrogate markers for efficacy in patients with HCC. [20][21][22] The prognostic value of these dermatologic AEs was also confirmed in our very recent multicentre clinical study of 606 HCC patients, which demonstrated that sorafenib-related dermatologic AEs may be used as clinical indicators to identify responders to sorafenib and those who are more likely to benefit from TACE-S treatment. 23 Indeed, patients who develop dermatologic AEs might constitute the ideal population in whom the addition of sorafenib would work.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, the significant differences found in these studies can be attributed to ignorance of the response to therapy. Because of the lack of reliable biomarkers for sorafenib use, dermatologic AEs related to sorafenib have become widely recognized as surrogate markers for efficacy in patients with HCC . The prognostic value of these dermatologic AEs was also confirmed in our very recent multicentre clinical study of 606 HCC patients, which demonstrated that sorafenib‐related dermatologic AEs may be used as clinical indicators to identify responders to sorafenib and those who are more likely to benefit from TACE‐S treatment .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In their cohort, HFS was not associated with OS or TTP, but BCLC stage was a negative independent prognostic factor [18]. In this regard, Ponziani et al found that adjustment of the sorafenib dose because of relevant side effects, to induce tolerability rather than stopping the drug, prolonged OS and TTP, and achieved even better results compared to the treatment group with minor side effects and unchanged treatment with 800 mg per day (OS 12.5 vs. 5.7 months, HR = 0.4, p < 0.0001, and TTP 9.5 vs. 3 months, HR = 0.3, p < 0.0001) [19]. A Japanese group performed a retrospective, propensity score matching analysis to investigate the effect of starting the treatment with an initial dosage of 400 mg per day vs. the recommended 800 mg per day (including the option to adjust the dose depending on tolerance and side effects).…”
Section: Biomarkers For Response To Targeted Systemic Therapy Withmentioning
confidence: 99%